If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.66 + 1 = 4x + -0.33 Combine like terms: 0.66 + 1 = 1.66 1.66 = 4x + -0.33 Reorder the terms: 1.66 = -0.33 + 4x Solving 1.66 = -0.33 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1.66 + -4x = -0.33 + 4x + -4x Combine like terms: 4x + -4x = 0 1.66 + -4x = -0.33 + 0 1.66 + -4x = -0.33 Add '-1.66' to each side of the equation. 1.66 + -1.66 + -4x = -0.33 + -1.66 Combine like terms: 1.66 + -1.66 = 0.00 0.00 + -4x = -0.33 + -1.66 -4x = -0.33 + -1.66 Combine like terms: -0.33 + -1.66 = -1.99 -4x = -1.99 Divide each side by '-4'. x = 0.4975 Simplifying x = 0.4975
| -4(n+7)-6n=-98 | | -5x-3=-20 | | 6n+8(n+3)=-2(2+2n)-8 | | 5=6w-9w-1 | | 16+3x+38=96 | | 16+3x+38+96=180 | | 7+4(1-4a)=-12+7a | | 5=6w-8w-1 | | x+0.1x=.017 | | 16x+3x+38=96 | | X^2+y^2+6X+2y+6=o | | -25=-10+1p | | 2p-5+7p=19+5p | | 2+5y=-3 | | 5y+3=3y-1 | | -5x+7y=1 | | 2r+2(5r+6)=-6+6r | | (4x-6)(8x+2)=0 | | (2x+3)(3x^2+2x-5)= | | 12y+180+6x=180 | | 138=-3(6n+2) | | x+3=152 | | 9s+3=67 | | 9x+7y=100 | | 0=10x+x^2-144 | | 5(-g-10)=6-13g | | 5+5n+5n=-15 | | (X+43)+(2x-73)=180 | | (7q-7)+(5q-9)= | | 6x+1=3(2x+1)-x+8 | | x+-5y=-3 | | 10x^2-45x-25=0 |